Sustainability Initiative towards Supply Chain Inventory Management - Bathool, Aysha (Recent Research Reviews Journal, 2022)
Almost every industrial supply chain operation has an environmental impact, ranging from pollution caused by industrial processes to waste generated by overproduction. The increased emission of greenhouse gases leads to global warming, demanding the use of sustainability initiatives in industrial supply chain models to reduce the emissions produced by their operations. The objective of this research study is to give a complete overview of integrating sustainability criteria into inventory management models to help researchers and practitioners make market-specific decisions. This study investigates simple and complex supply chain structures, as well as the incorporation of various green initiatives to improve the resiliency of supply chain models. The literature review highlights the sustainability constraints in inventory models by considering the industry’s environmental and societal consequences. Finally, through a detailed analysis of the existing literature and related limitations, this paper provides potential research insights for future research directions in the domain.